The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18466/cbayarfbe.533466
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity in Allium cepa L. Root Meristem Cells Exposed to the Herbicide Penoxsulam

Abstract: Penoxsulam is a new sulfonamide herbicide used on rice crops for annual grasses, broadleaf weeds, and sedges control, either grown through transplanting or direct dry or direct seeding methods of planting. In this study, Allium cepa ana-telophase and comet assay were used to examine the cyto-genotoxic effects of herbicide penoxsulam on A. cepa roots. A. cepa bulbs were exposed to ½xEC50 (12.5 µg/L), EC50 (25 µg/L) and 2xEC50 (50 µg/L) concentrations of penoxsulam for 24, 48, 72 and 96 h. Distilled water and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…Genotoxicity of the used herbicide is higher than normal with use of the highest concentration (1.6 ppm) for each application period. These outcomes agree with former studies (Ping et al, 2012;Karaismailoğlu et al, 2013;Karaismailoğlu, 2014bKaraismailoğlu, , 2015Bonciu et al, 2018;Liman and Özkan, 2019;Rosculete et al,2019;Aydın and Liman, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Genotoxicity of the used herbicide is higher than normal with use of the highest concentration (1.6 ppm) for each application period. These outcomes agree with former studies (Ping et al, 2012;Karaismailoğlu et al, 2013;Karaismailoğlu, 2014bKaraismailoğlu, , 2015Bonciu et al, 2018;Liman and Özkan, 2019;Rosculete et al,2019;Aydın and Liman, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In this work, sublethal impact has found in 1.6 ppm concentration when compared to the control in 12, 24 and 36 h treatments, and sublethal impact valuation are defined as 35.50%, 34.96% and 46.16%, respectively. The obtained outcomes are suitable with the results of the earlier works (Liman et al, 2011;Dragoeva et al, 2012;Karaismailoglu, 2015;Liman and Özkan, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…However, the application of blueberry extracts either alone or in combination with penoxsulam enhanced the mitotic index in a concentration-dependent manner emphasizing the protective role of blueberry extract. Similar inhibitory effects of penoxsulam on root growth and mitotic activity were reported by Özkan and Liman 63 . Panneerselvam et al .…”
Section: Discussionsupporting
confidence: 87%
“…In literature, there are records on the cytotoxicity and genotoxicity of sulfonamides. Özkan and Liman reported that the penoxsulam, is a sulfonamide herbicide, showed a cytotoxic effect by reducing MI, a genotoxic effect because it increased CA, which are stickiness, anaphase bridge, disturbed anaphasetelophase, chromosomal laggards, and polyploidy [7]. Badr (1982) analysed the cytogenetic effects of 3 sulphonamides, which were sulphadiazine, sulphadimidine, and sulphaphenazole and showed the mitotic and chromosomal abnormalities [21].…”
Section: (A) (B) (C) (D) (E) (F) (G) (H) (ı) (J) (K) (L) (M) (N) (O) (P) (R) (S)mentioning
confidence: 99%
“…The sulfasalazine (azulfidine), sulfamethoxazole (gantanol), sulfapiridine, sulfacetamide, and sulfadiazine, which are derivatives of sulfonamide and have a commercial market share, are important drug examples [6]. In addition, sulfonamide derivative are important compounds used as plant growth regulator [7]. The Allium test was first conducted by Levan (1938) to determine the effect of colchicine.…”
Section: Introductionmentioning
confidence: 99%